Does Competition Foster Efficiency? Empirical Evidence From Malaysian Commercial Banks - Ab Rahim, Rossazana (Asian Academy of Management (AAM), 2016)
This study focuses on technical efficiency measures and its decompositions as well as the relationship between efficiency and banking competition of Malaysian commercial banks. This study employs Data Envelopment Analysis to assess efficiency performance of Malaysian commercial banks during 1996–2011 while to estimate banking competition; Lerner index approach is utilised. Next, Granger causality tests between competition indexes and various measures of efficiency are undertaken to investigate "Does competition foster efficiency?" The evidence suggests that Malaysian commercial banks experienced increased concentration coupled with lower competition. The results of causality tests support a positive effect of competition on technical efficiency in Malaysian banking